Reducing the environmental and economic cost of metal extraction by optimal blast design - L Julian; W Hunt; R Pratama; D La Rosa; A Tsang (The Australasian Institute of Mining and Metallurgy, 2024)
Mineral extraction is facing the twin challenges of finite resources and increasing environmental and economic costs. Society’s growth is matched by an increase in demand for the earth’s resources. It is incumbent on us as contemporary mining professionals to promote and facilitate ethical and efficient practices. Technological developments have and will continue to allow a decrease in viable cut-off grades, creating new economic opportunities from deposits that were previously uneconomic. Mining low-grade deposits however, even with perfect recoveries, will have a significant environmental cost for the metal won. The greatest opportunity to increase metal with the least environmental cost is to increase the metal yield from existing mines. The determination of mining polygons is a critical juncture where rock is typically subjected to the binary grading of either ore or waste. This is undertaken using a number of factors, such as the mining equipment being used and the recovery in the processing plant. Traditionally, mining polygons were generated on the in situ grade control model. This ignores the complex differential blast dynamics that occur during blasting. Two opportunities exist to improve metal yields: optimise the blast design to achieve the post-blast muck pile that will support the greatest outcome; and generate optimised polygons on the post-blast muck pile. A data set from a Canadian Gold deposit is used to demonstrate the potential benefit of iterative blast movement modelling and grade control polygon optimisation on metal yield. The impact of blasting on the total recoverable metal is presented, highlighting blast design as a critical process in the mining value chain.